Implementasi Model Pembelajaran Scaffolding dalam meningkatkan keterampilan menulis karangan eksposisi pada mahasiswa PGSD - Halim, Patmawati (PEMBELAJAR: Jurnal Ilmu Pendidikan, Keguruan, dan Pembelajaran, 2017)
This study aims to describe the implementation of scaffolding learning model in improving writing skill exposition of PGSD 6th semester Pangkep student. The research design used in this research is the experimental research design that is inferential statistical type t test. The sample in this research is 28 students as experiment class. The result of this research is descriptive data of the implementation of scaffolding method in learning expositions of students writing PGSD illustrates that in the pretest results the average value achieved is 69.93, median 68.50, Std. Deviation 7,722, variant 59,62, highest value 84 and lowest value 60 with amount 1958. While at posttes average value reached is 76,75, median 80,00, Std. Deviation 8.601, its variant is 73,97, highest score 87 and lowest value 62 with amount of 2149. Result of t test of experimental value or result of prostes (tcount) obtained is = 47.220 with db 28-1 = 27 at significance level 5% and trust 95 % obtained ts 0.95 = 1.70 (can be seen in table). So t arithmetic = 47.220 and t table = 1.70 thus, t arithmetic> ttable. The hypothesis tested by t test statistic is the effectiveness of the implementation of scaffolding method in the learning of writing exposition composition on PGSD students. It turns t count (47.220)> t table (1.70). Based on these calculations, H0 is rejected and H1 (research hypothesis) is accepted. The result of the hypothesis shows that the implementation of scaffolding method in exposition writing has a significant influence on the improvement of writing expositions effectively on PGSD students.